SPE Asia Pacific Oil and Gas Conference and Exhibition 2013
DOI: 10.2118/165775-ms
|View full text |Cite
|
Sign up to set email alerts
|

Managed Pressure Drilling - A Solution for Drilling the Challenging and Un-Drillable Wells in Vietnam and South East Asia

Abstract: Managed Pressure Drilling (MPD) has been deployed in Vietnam for six (6) years since 2007 to address a number of drilling and reservoir challenges, and has delivered considerable success in many cases. Twenty five (25) separate projects have been performed over the six (6) year period, in a range of formations and with different types of rigs. The main application of MPD Technology has been in the following reservoir and formation types where the challenges are being encountered: granite basemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…MPD has been widely accepted throughout the drilling industry to date, and considerable numbers of case studies have demonstrated these benefits providing field data and engineering analysis. Several authors presented case studies where MPD system was successfully used to control influx and losses (Cenberlitas et al 2011;Qutob et al 2011;Gedge et al 2013;Kinik et al, 2014aKinik et al, , 2014bKinik et al, , 2015. The primary objective of MPD in these hydraulically challenged wells is to ensure the operational safety with less non-productive time to reach the target depth.…”
Section: Managed Pressure Drillingmentioning
confidence: 99%
“…MPD has been widely accepted throughout the drilling industry to date, and considerable numbers of case studies have demonstrated these benefits providing field data and engineering analysis. Several authors presented case studies where MPD system was successfully used to control influx and losses (Cenberlitas et al 2011;Qutob et al 2011;Gedge et al 2013;Kinik et al, 2014aKinik et al, , 2014bKinik et al, , 2015. The primary objective of MPD in these hydraulically challenged wells is to ensure the operational safety with less non-productive time to reach the target depth.…”
Section: Managed Pressure Drillingmentioning
confidence: 99%
“…presented micro flux control method which employs automatic choke system controlled by an intelligent control unit. The control system demonstrated promising results in a considerable number of case studies Vieira et al 2008;Cenberlitas et al 2011;Qutob et al 2011;Gedge et al 2013).…”
Section: Introductionmentioning
confidence: 99%